(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Poverty is one of the biggest problems of the 20th century. More than three billion people live in poverty in this world. Muslim societies lag far behind the rest of the world in addressing poverty. According to database of the World Bank (2021), approximately 698 million people, or 9 percent of the world’s population, live in extreme poverty. They have an income of less than 1.90 US dollars a day. One of the main causes of poverty is limited access to financial services. Unlike commercial banks, microfinance organizations were established and are developing as a financial mechanism that serves the population with low income. This article mainly covers the types of Islamic microfinance and its role in reducing poverty. Scientifically based proposals and recommendations on the establishment of an Islamic microfinance organization in Uzbekistan have been developed.